My Tourist Guide to the Solar System And Beyond - Dartnell, Lewis; Illustrated by Kuntton, Katie (London Dorling Kindersley, 2012)
By way of a quirky guidebook approach, young readers will survey the lay of the land by hiking the Mariner Valley on Mars, collecting icy pebble souvenirs from a flight through Saturn's rings, and bouncing on the gravity-light moon Enceladus. Stunning images and photographs combine with text boxes detailing 'Things to see' and 'What to pack' to create an out-of-this-world experience for all.
Includes Color Illustrations
Keywords: Planets -- Solar System -- Asteroid Belt